11β-Hydroxysteroid Dehydrogenase 2 in Preeclampsia - Katarzyna Kosicka; Anna Siemiątkowska; Franciszek K. Główka (International Journal of Endocrinology)
Preeclampsia is a serious medical problem affecting the mother and her child and influences their health not only during the pregnancy, but also many years after. Although preeclampsia is a subject of many research projects, the etiology of the condition remains unclear. One of the hypotheses related to the etiology of preeclampsia is the deficiency in placental 11β-hydroxysteroid dehydrogenase 2 (11β-HSD2), the enzyme which in normal pregnancy protects the fetus from the excess of maternal cortisol. The reduced activity of the enzyme was observed in placentas from pregnancies complicated with preeclampsia. That suggests the overexposure of the developing child to maternal cortisol, which in high levels exerts proapoptotic effects and reduces fetal growth. The fetal growth restriction due to the diminished placental 11β-HSD2 function may be supported by the fact that preeclampsia is often accompanied with fetal hypotrophy. The causes of the reduced function of 11β-HSD2 in placental tissue are still discussed. This paper summarizes the phenomena that may affect the activity of the enzyme at various steps on the way from the gene to the protein.